Validity and Reliability of the Dying Care Process and Outcome Scales Before and After Death From the Bereaved Family Members' Perspective. (February 2019) - Kanno, Yusuke; Sato, Kazuki; Shimizu, Megumi; Funamizu, Yuko; Andoh, Hideaki; Kishino, Megumi; Senaga, Tomomi; Takahashi, Tetsu; Miyashita, Mitsunori
Objective: There are no instruments evaluating the processes and outcomes of dying care right before and after death. Therefore, we developed and examined the validity and reliability of 2 scales for evaluating dying care processes and outcomes before and after death. Methods: A cross-sectional, anonymous questionnaire was administered to bereaved family members of patients with cancer who had died in 5 facilities. We evaluated the Dying Care Process Scale for Bereaved Family Members (DPS-B) and the Dying Care Outcome Scale for Bereaved Family Members (DOS-B) with 345 bereaved family members. Results: A factor analysis revealed that DPS-B and DOS-B each consisted of 4 subscales. For the DPS-B, they were "symptom management, " "respect for the patient's dignity before and after death, " "explanation to the family, " and "family care." For the DOS-B, they were "peaceful dying process for the patient, " "being respected as a person before and after death, " "good relationship between the patient and family, " and "peaceful dying process for the family." Both DPS-B and DOS-B had sufficient convergent and discriminative validity, sufficient internal consistency (DPS-B: α = 0.91 and subscales' αs = 0.78-0.91; DOS-B: α = 0.91 and subscales' αs = 0.78-0.94), and sufficient test–retest reliability (DPS-B: intraclass correlation coefficient [ICC] of total score = 0.79 and subscales = 0.55-0.79; DOS-B: ICC of total score = 0.88 and subscales = 0.70-0.88). Significance of Results: Both DPS-B and DOS-B are valid and reliable scales for evaluating the dying care processes and outcomes before and after death from the bereaved family members' perspectives.